SQL Logic Error Detection using Start End Mid Algorithm - Ardiansyah, Jevri Tri; Wibawa, Aji Prasetya; Widiyaningtyas, Triyanna; Yasuhisa, Okazaki (Knowledge Engineering and Data Science, 2018)
Database is an important part of a system and it stores data to be manipulated. SQL (Structured Query Language) is used for manipulating those data to extract information and make decision. There are two types of error which make SQL is challenging to learn, namely syntax error and logic error. Compiler can detect syntax error, but it does not show error warning while logical error occurred. It makes logic error more difficult to understand than syntax error. A web based SQL compiler with errors detection ability by using Start End Mid algorithm is then developed, To help database's user to learn SQL in practical implementation.